2021
DOI: 10.1038/s41598-021-95905-8
|View full text |Cite
|
Sign up to set email alerts
|

High taxonomic resolution surveys and trait-based analyses reveal multiple benthic regimes in North Sulawesi (Indonesia)

Abstract: As coral reef communities change and reorganise in response to increasing disturbances, there is a growing need for understanding species regimes and their contribution to ecosystem processes. Using a case study on coral reefs at the epicentre of tropical marine biodiversity (North Sulawesi, Indonesia), we explored how application of different biodiversity approaches (i.e., use of major taxonomic categories, high taxonomic resolution categories and trait-based approaches) affects the detection of distinct fish… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The current 'flattening' of reefs will have, at present largely unknown, ecological consequences as cryptic communities, with largely understudied ecological functions, may disappear accordingly. Studies assessing coral reef trajectories and recovery after disturbances should incorporate a functional assessment of the communities as recent studies have shown that cover estimates or alpha diversity measures can mask important changes (McWilliam et al, 2020;Reverter et al, 2021;Richardson et al, 2018). Furthermore, novel threats, such as the increase of pathogens linked to climate change or anthropogenic substances (e.g.…”
Section: Con Clus I On S and Future Direc Tionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current 'flattening' of reefs will have, at present largely unknown, ecological consequences as cryptic communities, with largely understudied ecological functions, may disappear accordingly. Studies assessing coral reef trajectories and recovery after disturbances should incorporate a functional assessment of the communities as recent studies have shown that cover estimates or alpha diversity measures can mask important changes (McWilliam et al, 2020;Reverter et al, 2021;Richardson et al, 2018). Furthermore, novel threats, such as the increase of pathogens linked to climate change or anthropogenic substances (e.g.…”
Section: Con Clus I On S and Future Direc Tionsmentioning
confidence: 99%
“…In fact, recent research suggests that coral reefs dominated by invertebrates other than hard corals, such as sponges and soft corals, might be becoming more frequent as a result of global change (Bell et al, 2018;Chaves-Fonnegra et al, 2018;Inoue et al, 2013;Lesser & Slattery, 2020). Yet, information regarding changes to such alternative communities remain highly scattered and the drivers and mechanisms behind the proliferation of these alternative organisms remain largely unknown (Norström et al, 2009;Reverter et al, 2021). For example, whereas some changes have been observed after specific pulse disturbances, such as bleaching events (Chaves-Fonnegra et al, 2018) or ocean acidification (Inoue et al, 2013), their frequency, distribution and implications for ecosystem functioning remain unexplored.…”
Section: Introductionmentioning
confidence: 99%